A comparative analysis of exchange rate volatility in the West African Monetary Zone - Abayomi T. Onanuga; Olaronke T. Onanuga (CBN Journal of Applied Statistics, 2015)
This study employs measures of variability and three GARCH models to comparatively explore the behaviour of exchange rate volatility of the currencies in the West African Monetary Zone (WAMZ) for the period 1960M01-2011M12. The study selects a sub-sample period of 2000M1 to 2011M12 to investigate whether central bank intervention decreases volatility of the local currencies per US. Our findings reveal that the Ghanaian cedi is the most volatile currency in the Zone. Also, we found that leverage effect does exist for Gambian dalasi, while it does not exist for Nigerian naira; but inconclusive for other countries. The impact of central bank intervention on exchange rate volatility is also found to be inconclusive for Ghana, Guinea, and Liberia. However, the impact of central bank intervention on foreign exchange decreases the level of volatility persistence in Gambia and Nigeria, while it increases the level of volatility persistence in Sierra Leone for the period under consideration.
Keywords: C10; F31; 330; Exchange rate; Volatility; GARCH; West African Monetary Zone